Airway Management Proficiency Checklist for Assessing Paramedic Performance. (4th May 2017) - Way, David P.; Panchal, Ashish R.; Finnegan, Geoffrey I.; Terndrup, Thomas E.
Abstract: Objective : To develop and derive an instrument for assessing airway management proficiency for paramedics.Methods : Using a validated difficult airway model simulation, we recorded responses to a standard traumatic brain injury scenario requiring airway management in 197 certified paramedics. Discrete items ( N = 131) were developed by an expert panel, and referenced to three performance standard subscales (i.e., intubation, ventilation, and backup airway). Responses were scored and subjected to an iterative process to create a more practical number of items for the final Airway Management Proficiency Checklist (AMPC). Tetrachoric correlations were used to evaluate items for relevance. Kuder-Richardson Formula 20 reliabilities were used to assess internal consistency among checklist items. Finally, a Rasch analysis on each subscale was performed to evaluate items for measurement quality. Items were retained if they were determined to fit the Rasch Model.Results : Items were deleted from the final AMPC for lack of simulation fidelity (26 items), duplicity (15 items), and poor psychometric quality (39 items). In four additional iterations, items were dropped for lack of equipment options (e.g., single mask), lack of instructional clarity (e.g., calculation of GCS score), high inference on the part of the evaluator (6 items), or inadequate measurement of behavioral performance (e.g., passes blade through lips without contacting mouth or teeth). Thirty seven items and three outcome standards (first pass success of the endotracheal tube; assisted ventilation with no interruption of 30 seconds or greater; successful placement of a backup airway device within one attempt) were retained to form three hypothesized subscales.Conclusions : The AMPC represents a psychometrically derived instrument that identified important tasks required for comprehensive airway management. The 37-item instrument will contribute to improving training and measuring the performance of paramedic's airway management skills.